Managers' trait affectivity and cognitive ability as drivers of business practices - Huong Trang Kim (Cogent Business & Management, 2021)
An under-researched question is to what extent managers' trait affectivity and cognitive ability play a role in driving business practices. As such, we carry out a survey with 623 textile and garment firms in Vietnam. We find that one standard deviation decrease in the managers' negative affectivity is associated with a 2.28% increase in business practices. Additionally, increasing managers' positive affectivity and cognitive ability levels by one point would lead to 1.836% and 2.16% higher business practices, respectively. Notably, these effects on marketing practices are strongest. We also found evidence that decision-making on business practices in large firms largely depends on managers' trait affectivity. At the same time, the cognitive ability of managers in SMEs has a strong effect on business practices.
Keywords: G41; D22; D91; 650; Trait affectivity; cognitive ability; business practices; survey; managers